Tryptophan Catabolism in Chronic Viral Infections: Handling Uninvited Guests - Mehraj, Vikram (Int J Tryptophan Res, 2015)
l-Tryptophan (l-Trp) is an essential amino acid that possesses diverse metabolic, neurological, and immunological roles spanning from the synthesis of proteins, neurotransmitter serotonin, and neurohormone melatonin, to its degradation into immunosuppressive catabolites by indoleamine-2, 3-dioxygenase (IDO) in the kynurenine pathway (KP). Trp catabolites, by activating aryl hydrocarbon receptor (AhR), play an important role in antimicrobial defense and immune regulation. IDO/AhR acts as a double-edged sword by both depleting l-Trp to starve the invaders and by contributing to the state of immunosuppression with microorganisms that were not cleared during acute infection. Pathogens experiencing Trp deprivation by IDO-mediated degradation include certain bacteria, parasites, and less likely viruses. However, chronic viral infections highjack the host immune response to create a state of disease tolerance via kynurenine catabolites. This review covers the latest data involving chronic viral infections such as human immunodeficiency virus (HIV), hepatitis B virus (HBV), hepatitis C virus (HCV), herpes, and cytomegalovirus (CMV) and their cellular interplay with Trp catabolites. Strategies developed by viruses to escape immune control also represent new avenues for therapeutic interventions based on Trp metabolism.